Proses Penghalusan Permukaan Spesimen Dari Bahan Abs Yang Dibentuk Melalui Rapid Tooling - Laksono, Ganang Puji, Bambang W. Febriantoko, ST, MT, Ir. Bibit Sugito, MT (2016)
Information and analysis about the result of the process 3d printing in indonesia there is very few like the roughness objects resulting from the process. Things like is very important to note , that products which will produced according to a hoped-for goal. The purpose of this study is to find the influence of material abs of the printer 3D through process of smoothing the surface chemically and mechanical with this photo micro and to obtain as a price value Ra (µm) best from the process of smoothing the surface chemically and mechanical with this surface roughness (surface roughness a tester) This research use of acrylonitrile butadiene styrene (ABS) formed to specimens and mashed and in test with a test roughness (roughness a tester type TR200 with a standard ISO 1302) with variations material abs the process acetone 6ml , the process sandpaper 5000 smoothed for 6 , 8 and 10 minutes , as products being without process of smoothing the surface Of testing roughness so the results average score roughness average (Ra) in a specimen without rarefaction the surface is 8,886 µm. As for specimens avocado acetone 6ml for 6, 8 and 10 minutes it has value the average Ra of 0,918 µm, and specimens avocado with sandpaper 5000 for 6 , 8 and 10 it has value the average ra of 0,253 µm. So that the rate fineness to which is the best in the printer 3D here the most optimal where the specimens avocado mechanically use sandpaper 5000.